Central Bank Swap Lines - Saleem Bahaj; Ricardo Reis (Center for Economic Studies and ifo Institute (CESifo), 2018)
Swap lines between advanced-economy central banks are a new important part of the global financial architecture. This paper analyses their monetary policy effects from three perspectives. First, from the perspective of the central banks, it shows that the swap line mimics discount-window credit from the source central bank to the recipient-country banks using the recipient central bank as the bearer of the credit risk. Second, from the perspective of the transmission of monetary policy, it shows that the swap-line rate puts a ceiling on deviations from covered interest parity, and finds evidence for it in the data. Third, from the perspective of the macroeconomic effects of policy, it shows that the swap line ex ante encourages inflows from recipient-country banks into assets denominated in the source-country's currency by reducing the ex post funding risk. We find support for these predictions using difference-in-difference empirical strategies that exploit the fact that only some currencies saw changes in the terms of their dollar swap line, only some bonds in banks' investments are exposed to dollar funding risk, only some dollar bonds are significantly traded by foreign banks, and only some banks have a significant U.S. presence.
Keywords: E44; F33; G15; 330; liquidity facilities; currency basis; bond portfolio flows